Production of natural coagulant from Moringa oleifera seed for drinking water treatment - Ali, Eman N; Muyibi, Suleyman Aremu; Mohd. Salleh, Hamzah; Alam, Md. Zahangir; Salleh, Mohd Ramlan M. (IWA Publishing, 2010)
Water treatment industry worldwide including South East Asia IS facing high demand for synthetic coagulants for water treatment process. Research is continuously being done to find the best treatment methods and lower cost alternatives. Moringa oleifera seed could be a suitable natural alternative to synthetic coagulants. This paper investigates processing Moringa oleifera seed in order to concentrate the bio-active constituents which have coagulation activity. The proposed method to isolate and purify the bio-active constituents is the cross flow filtration method, which produced the natural coagulant with very cost effective processing technique (oil extraction; salt extraction; and microfiltratlon through 0.20 ~Im). Coagulation activity was determined using conventional jar test procedures, and the major water quality control parameters monitored was the residual turbidity for river water with low initial turbidity. Results showed residual turbidity of less than 5 NTU which is recommended by the World Health Organization (WHO). The turbidity removal was 94.82% for river water of low initial turbidity of 44.2 NTU, without any chemicals added. The microfiitration method is considered to be a practical method which needs no chemicals added. The product is commercially valuable and can contribute to the economic development of South East Asian countries.